2019
DOI: 10.15344/2456-8171/2019/139
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection Afforded by a Preventive CogniXtra Treatment Against Amyloid Beta Aβ25-35 Peptide-induced Toxicity in Mice

Abstract: carnitine, coenzyme Q10, polyphenols, ginkgo biloba, long chain polyunsaturated fatty acids -PUFAs) have been devoted a lot of attention [10,11].In this paper we investigate the neuroprotective efficacy of docosahexaenoic acid (DHA), glutathione (GSH), phosphatidylcholine (PC), curcumin (CUR) and resveratrol (RES) given alone or in combination for thirty consecutive days as a preventive treatment in a well recognized mouse model of AD. This model consists in a unique intracerebroventricular (i.c.v.) injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
2
0
4
Order By: Relevance
“…Blivet et al. showed that PBM could rescue the neurotoxicity induced by Aβ25–35 in mice [104] . Recently, pilot clinical trials with dementia and AD patients suggested that PBM could lead to significant cognitive improvement [134]…”
Section: Molecular Light For Photo‐biomodulation (Pbm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Blivet et al. showed that PBM could rescue the neurotoxicity induced by Aβ25–35 in mice [104] . Recently, pilot clinical trials with dementia and AD patients suggested that PBM could lead to significant cognitive improvement [134]…”
Section: Molecular Light For Photo‐biomodulation (Pbm)mentioning
confidence: 99%
“…Considering that our human evolution is accompanied by light, it is not surprising that light has tremendous effects on our health. The PBM effects of natural sunlight and physically generated light have been comprehensively investigated [104] . For example, in 1980, Lewy et al.…”
Section: Molecular Light For Photo‐biomodulation (Pbm)mentioning
confidence: 99%
“…Yüksek dolaşımdaki serum asprosin düzeylerinin, NAFLD hastaların insülin direncinde de rol oynadığı ve NAFLD'nin ayırıcı tanısı için umut verici yeni bir biyobelirteç olabileceği gösterilmiştir (48). Bununla birlikte, son zamanlarda NAFLD'li hastada yapılan bir çalışmadan elde edilen veriler, bu hastalarda serum ve tükürük asprosin düzeylerinin kontrol grubuyla karşılaştırıldığında anlamlı derecede düşük olduğunu gösterdi (49).…”
Section: Asprosin Ve Non-alkolik Yağlı Karaciğer Hastalığı (Nafld)unclassified
“…48 Benzer durum, PMS semptomlu kadınlarda da gözlenmiş olup, su tutulumunun luteal fazda foliküler faza göre daha yüksek olduğu belirlenmiştir. 49 Farklı olarak, menstrüel siklusun evrelerine göre, vücut kompozisyonunda anlamlı düzeyde farklılığın görülmediğini bildiren çalışmalar da bulunmaktadır. 50,51…”
Section: Menstrüel Si̇klusun Vücut Ağirliği üZeri̇ne Etki̇si̇unclassified
See 1 more Smart Citation